How much do financial analysts disagree on the future path of the ECB's interest rate? - Alexander Glas; Julius Schölkopf (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
On 6 June 2024, the European Central Bank (ECB) lowered the main refinancing operations (MRO) rate from 4.5% to 4.25%. This decision followed a period of elevated interest rates intended to combat high inflation in the euro area, which peaked at 10.6% in October 2022 in the aftermath of the COVID-19 pandemic and the Russian invasion of Ukraine. Although inflation levels are now closer to the ECB's medium-term target of 2%, some doubt remains on whether the inflationary pressure has truly abated, since the last mile of the inflation cycle is often perceived as challenging. Indeed, inflation increased again in May 2024 to 2.6%, from 2.4% in April, and the ECB has not committed itself to a certain interest rate path. Instead, it follows a data-dependent meeting-by-meeting approach for further interest rate decisions. In this policy brief, we analyse whether and how much professional forecasters and market analysts disagree on the nature and speed of future interest rate decisions by the ECB. We also consider the role of uncertain dynamics of future inflation and the economic recovery in the euro area to explain the dispersion of interest rate expectations. For this purpose, we asked the participants in the June 2024 wave of the ZEW's Financial Market Survey for their expectations regarding interest rate decisions at upcoming Governing Council meetings. We condition the individual responses on the respondents' short- and medium-term inflation and GDP growth expectations and supplement our findings with similar evidence for the US.
Keywords: 330